1981
DOI: 10.1111/j.1476-5381.1981.tb08736.x
|View full text |Cite
|
Sign up to set email alerts
|

Atropine and Micturition Responses by Rats With Intact and Partially Innervated Bladder

Abstract: 1 Micturition responses by a group of 17 rats were recorded during a water diuresis. During a 2 h period, uniform volumes of urine were passed at regular intervals; the mean of the voiding responses by each animal was consistent from one water loading period to another. Residual urine volumes were physiologically insignificant. 2 Atropine treatment did not compromise seriously micturition by water-loaded rats. Treated animals micturated more frequently; the mean volume was 68% of control. The residual urine vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1985
1985
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
(22 reference statements)
0
13
1
Order By: Relevance
“…Unlike the situation in conscious rats [Carpenter, 1981;Yaksh et al, 1986;Monkawa et al, 19891, we found that all anesthetized rats had certain amount of fluid retained within the bladder after micturition. Previous studies also reported residual volume [Kruse et al, 1993;Mallory et al, 1989;Maggi et al, 19861.…”
Section: Characteristics Of Flow Rate and Bladder Pressure In Female contrasting
confidence: 79%
“…Unlike the situation in conscious rats [Carpenter, 1981;Yaksh et al, 1986;Monkawa et al, 19891, we found that all anesthetized rats had certain amount of fluid retained within the bladder after micturition. Previous studies also reported residual volume [Kruse et al, 1993;Mallory et al, 1989;Maggi et al, 19861.…”
Section: Characteristics Of Flow Rate and Bladder Pressure In Female contrasting
confidence: 79%
“…The bladder rapidly adapts to increased urine production by increasing micturition frequency and volume (21). It was reported that an increase in water intake can increase bladder capacity within minutes (1). Such a resetting of the threshold volume for initiating a micturition reflex may involve nervous mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Elimination was linear during the 2 h required for the water to be excreted (Carpenter, 1981 A mean volume threshold (MV) of 2.5 ± 0.1 ml (s.e.mean) was obtained in a group of 16 rats before the administration of morphine sulphate. In all but one animal the MV of each rat was increased nearly 40% above its own control by morphine sulphate (5 mg kg-') and the group mean was increased to 3.4 ± 0.1 ml.…”
Section: Resultsmentioning
confidence: 99%
“…It appears likely that morphine, acting upon specific opioid receptors, interferes with these reflex pathways (Dray & Metsch, 1984). To this end it seemed reasonable to examine the action of morphine on micturition of conscious rats; the threshold to induce voiding may be measured repeatedly in rats made to void by water loading (Carpenter, 1981). Moreover, the efficacy of micturition can also be assessed by a determination of the urine volume remaining in the bladder when voiding is completed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation